2002
DOI: 10.1103/physrevlett.89.025001
|View full text |Cite
|
Sign up to set email alerts
|

Fast Electron Transport in Ultraintense Laser Pulse Interaction with Solid Targets by Rear-Side Self-Radiation Diagnostics

Abstract: We report on rear-side optical self-emission results from ultraintense laser pulse interactions with solid targets. A prompt emission associated with a narrow electron jet has been observed up to aluminum target thicknesses of 400 microm with a typical spreading half-angle of 17 degrees. The quantitative results on the emitted energy are consistent with models where the optical emission is due to transition radiation of electrons reaching the back surface of the target or due to a synchrotron-type radiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 18 publications
3
79
0
Order By: Relevance
“…[18][19][20] These pioneering works lead to the establishment of scaling laws for the laser-to-electron energy conversion efficiency, 7,9,10 the electron beam current average velocity, 6 and divergence. 11,12,15,16 Other experiments were devoted to measure the range, the collimation of these electrons, and the way they lose their energy while propagating through solid samples, either foils, 8,9,13,14,17 wire targets, 21,22 or 1D-compressed foils. 18,19,23 Nonetheless, using solid or even 1D-compressed targets strongly limits the area of investigation to low temperatures (<10 eV) and moderate densities (<5g=cm 3 ), which are far from the plasma parameters of the compressed core of a driven ICF target (100 g=cm 3 , 300 eV).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] These pioneering works lead to the establishment of scaling laws for the laser-to-electron energy conversion efficiency, 7,9,10 the electron beam current average velocity, 6 and divergence. 11,12,15,16 Other experiments were devoted to measure the range, the collimation of these electrons, and the way they lose their energy while propagating through solid samples, either foils, 8,9,13,14,17 wire targets, 21,22 or 1D-compressed foils. 18,19,23 Nonetheless, using solid or even 1D-compressed targets strongly limits the area of investigation to low temperatures (<10 eV) and moderate densities (<5g=cm 3 ), which are far from the plasma parameters of the compressed core of a driven ICF target (100 g=cm 3 , 300 eV).…”
Section: 2mentioning
confidence: 99%
“…To understand both points, numerous experiments were realized using solid targets [6][7][8][9][10][11][12][13][14][15] and a few with 1D laser-compressed targets. [18][19][20] These pioneering works lead to the establishment of scaling laws for the laser-to-electron energy conversion efficiency, 7,9,10 the electron beam current average velocity, 6 and divergence.…”
Section: 2mentioning
confidence: 99%
“…The equilibrium between fast electron beam and the return currents is unstable for the Weibel instabilities, which will produce strong electromagnetic perturbation and filaments of fast electron beam. It makes the energy transport effectiveness very poor and the intense fast electrons cannot transport beyond the filament length [8][9][10][11][12][13]. For any useful applications, it is therefore of great interest to find methods to weaken Weibel instabilities and increase the transport distance of intense fast electron beams in overdense plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Various diagnostic methods have been used to measure the fast electron divergence, such as K a X-ray emission [10], shadowgraphy [11], optical self-emission from the rear surface [12], and proton emission [13]. It is generally found that the divergence measured in the experiments increases with laser intensity [14], though some discrepancy exists among the different diagnostic methods because each one is dependent on different parameters [11].…”
Section: Introductionmentioning
confidence: 99%